The Role of Tasawuf in Improving the Spiritual and Work Ethos of Urban Communities: A Case Study of Tarekat Tijaniyah in Mampang Prapatan, Jakarta Selatan - MU’IN, Fathul (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:This paper examines the influence of the Tarekat Tijaniyah on its adherents' spiritual development and work ethic. Methodology:The type of research used is qualitative research with a case study approach: the tarekat Tijaniyah in Mampang Prapatan, South Jakarta. The primary data sources in this study are the results of observation and interview data obtained from the objects and research subjects. The secondary data source is literature related to the tasawuf and tarekat, obtained from books and scientific research results. The data were analyzed using a phenomenological approach. Findings:The study results show that the tarekat has influenced the changes in its congregation in terms of its spiritual and work ethic. The tarekat has become a driving force for social behavior changes, a mindset in the meaningfulness of life, and an increase in obedience and sincerity in worship.